DWRV a study on its credibility and effectivity as an AM medium - Abriam, Rikka Mae Bassi; Taoaguen, Rosemarie Gorospe (2000)
The main objective of this study is to determine the credibility and effectivity of DWRV Radio Veritas an an AM mass communication medium. This study is also concerned in finding out how the reporters of DWRV assess the broadcasting management of the station. A survey conducted among 100 residents of Bayombong, Nueva Vizcaya. In order to achieve a balanced presentation, Fifty of the respondents were Roman Catholics while the other half were non-Roman Catholics. Furthermore, questionnaires were distributed to DWRV staff and reporters because the researchers deemed their perception as essential in a complete and fair analysis and interpretation of this study. Findings of this study showed that majority of the respondents perceive DWRV as a credible and effective AM station. Also, results indicated that there exists a freedom of expression in the station although this is subjected to certain limitations -- Author's abstract.
Thesis (Bachelor of Arts) -- University of the Philippines Baguio, 2000.
Includes bibliographical references.
Keywords: DWRV (Radio station : Nueva Vizcaya, Philippines); Radio stations -- Philippines -- Bayombong (Nueva Vizcaya)